Strategies for Enhancing the Distribution of Islamic Subsidized Housing Financing to Low-Income Communities in the Bogor Region - Abdul Mutolib; Muhamad Findi Alexandi; Budi Suharjo (Economics and Digital Business Review, 2026)
Home ownership is a basic need for everyone, especially those already married. However, home ownership remains a challenge for low-income communities. To meet this housing need, the government, through the Ministry of Public Works and Public Housing (PUPR), provides adequate housing for low-income communities (MBR) by providing subsidies through People's Housing Credit (KPR). Bank Syariah Indonesia (BSI) supports subsidized KPR for MBR in West Java. The objectives of this study are: (1) to analyze the increase in the distribution of subsidized home ownership financing in the Bogor region, (2) to analyze the factors influencing the increase in the distribution of subsidized home ownership financing in the Bogor region, and (3) to analyze alternative strategies for the distribution of subsidized home ownership financing in the Bogor region. The data used are primary data from questionnaires and interviews, as well as secondary data from library research and literature reviews. The sampling technique used was non-probability-based sampling. The sample consisted of 258 BSI customers applying for subsidized home ownership financing. The data analysis used in this study included descriptive analysis, SWOT analysis, and QSPM. The results showed that the appropriate strategy was a growth and development strategy, with the primary strategy being to tighten the financing feasibility analysis to minimize the risk of non-performing loans. This strategy was prioritized because the company needed to maintain financing quality and minimize the risk of non-performing loans amidst fluctuating economic conditions. Furthermore, maintaining the superiority of sharia contracts and optimizing digital marketing were also important priority strategies to increase the company's competitiveness.